How Effective is Monetary Transmission in Low-Income Countries? : A Survey of the Empirical Evidence - Mishra, Prachi (IMF Working Papers; Working Paper ;, 2012)
This paper surveys the evidence on the effectiveness of monetary transmission in low-income countries. It is hard to come away from this review with much confidence in the strength of monetary transmission in such countries. We distinguish between the "facts on the ground" and "methodological deficiencies" interpretations of the absence of evidence for strong monetary transmission. We suspect that "facts on the ground" are an important part of the story. If this conjecture is correct, the stabilization challenge in developing countries is acute indeed, and identifying the means of enhancing the effectiveness of monetary policy in such countries is an important challenge.